An error or not an error? : ESL students’ identification and correction of errors / Sheema Liza Idris and Kamisah Ariffin - Idris, Sheema Liza; Ariffin, Kamisah (Universiti Teknologi MARA Cawangan Pahang, 2007)
Research has emphasised that errors can be an effective means of improving language learning, particularly grammatical accuracy. The most common practice in the field of error analysis is identifying and analysing errors in students’ language production. The present study differs from the empirical ones as it focuses on students’ ability and strategies in identifying and correcting pre-determined errors in given texts rather than the students’ own written production. It is the assumption of the study that if students are not able to perceive the errors as errors, they will continuously commit errors which, in turn, may lead to the incessant incorrect and inappropriate use of the language. Thus, the findings of the study would allow for an in-depth analysis of students’ linguistic skills and provide some suggestions for more effective instructional practice to language instructors.